PGE2-EP2/EP4 signaling elicits mesoCAR T cell immunosuppression in pancreatic cancer - Akbari, Behnia; Soltantoyeh, Tahereh; Shahosseini, Zahra; Jadidi-Niaragh, Farhad; Hadjati, Jamshid; Brown, Christine E.; Mirzaei, Hamid Reza (Frontiers in Immunology, 2023)
For many years, surgery, adjuvant and combination chemotherapy have been the cornerstone of pancreatic cancer treatment. Although these approaches have improved patient survival, relapse remains a common occurrence, necessitating the exploration of novel therapeutic strategies. CAR T cell therapies are now showing tremendous success in hematological cancers. However, the clinical efficacy of CAR T cells in solid tumors remained low, notably due to presence of an immunosuppressive tumor microenvironment (TME). Prostaglandin E2, a bioactive lipid metabolite found within the TME, plays a significant role in promoting cancer progression by increasing tumor proliferation, improving angiogenesis, and impairing immune cell’s function. Despite the well-established impact of PGE2 signaling on cancer, its specific effects on CAR T cell therapy remain under investigation. To address this gap in knowledge the role of PGE2-related genes in cancer tissue and T cells of pancreatic cancer patients were evaluated in-silico. Through our in vitro study, we manufactured fully human functional mesoCAR T cells specific for pancreatic cancer and investigated the influence of PGE2-EP2/EP4 signaling on proliferation, cytotoxicity, and cytokine production of mesoCAR T cells against pancreatic cancer cells. In-silico investigations uncovered a significant negative correlation between PGE2 expression and gene signature of memory T cells. Furthermore, in vitro experiments demonstrated that the activation of PGE2 signaling through EP2 and EP4 receptors suppressed the proliferation and major antitumor functions of mesoCAR T cells. Interestingly, the dual blockade of EP2 and EP4 receptors effectively reversed PGE2-mediated suppression of mesoCAR T cells, while individual receptor antagonists failed to mitigate the PGE2-induced suppression. In summary, our findings suggest that mitigating PGE2-EP2/EP4 signaling may be a viable strategy for enhancing CAR T cell activity within the challenging TME, thereby improving the efficacy of CAR T cell therapy in clinical settings.